Analisis Pengetahuan Ibu Hamil tentang Pemeriksaan Ibu Hamil Selama Masa Covid 19 di Wilayah Kerja Puskesmas Sukaraja Kota Bandar Lampung - Dina Martiani; Aryanti Wardiyah; Rilyani Rilyani (Malahayati Nursing Journal, 2023)
ABSTRACT Pregnancy is when a woman's immune state is compromised, and adaptive biological changes from time to time during pregnancy can make women more susceptible to viral infections. The Indonesian Association of Obstetrics and Gynecology (POGI) reported that 536 pregnant women were infected with the corona virus in a one-year period, and 3% were confirmed to have died. It is known that the knowledge of pregnant women regarding the examination of pregnant women during the Covid-19 period in the work area of the Sukaraja Health Center, Bandar Lampung City, in 2023. This type of quantitative research, with a descriptive research design. The population of all pregnant women is 272 people, the sample is 162 respondents using the Proportionate Stratified Random Sampling method. Collecting data using questionnaires and using univariate data analysis. It is known that the respondents' knowledge about the schedule of visiting pregnant women during the Covid-19 period in the work area of the Sukaraja Public Health Center, Bandar Lampung City in 2023, was mostly in the category of poor knowledge as many as 94 respondents (56%). It is recommended that pregnant women routinely participate in counseling or health education activities conducted by health workers, so as to create a good quality pregnancy and can reduce maternal mortality. Keywords: Knowledge, Pregnant Women, Covid Times  ABSTRAK Kehamilan merupakan dimana keadaan imun seorang wanita sedang terganggu, dan perubahan adaptif biologis dari waktu ke waktu selama hamil dapat membuat wanita lebih rentan terinfeksi virus. Perkumpulan Obstetri dan Ginekologi Indonesia (POGI) melaporkan terdapat 536 ibu hamil terinfeksi virus corona dalam periode waktu satu tahun, dan terkonfirmasi 3% meninggal dunia. Diketahui pengetahuan ibu hamil tentang pemeriksaan ibu hamil selama masa covid-19 di wilayah kerja Puskesmas Sukaraja Kota Bandar Lampung Tahun 2023.  Jenis penelitian kuantitatif, dengan rancangan penelitian deskriptif. Populasi seluruh ibu hamil sebanyak 272 orang, sampel sebanyak 162 responden dengan metode Proportionate Stratified Random Sampling. Pengumpulan data menggunakan lembar kuesioner dan menggunakan analisa data univariat.  Diketahui bahwa pengetahuan responden  tentang jadwal kunjungan ibu hamil selama masa covid-19 di wilayah kerja Puskesmas Sukaraja Kota Bandar Lampung Tahun 2023, sebagian besar dengan kategori pengetahuan kurang baik sebanyak 94 responden (56%). Disarankan ibu hamil rutin berpartisipasi dalam kegiatan penyuluhan atau pendidikan kesehatan yang dilakukan petugas kesehatan, sehingga tercipta kualitas kehamilan yang baik dan dapat menurunkan angka kematian ibu. Kata Kunci: Pengetahuan, Ibu Hamil, Masa Covid